The formation and structure of a rare fog at Jodhpur - RAO , D. VENKATESWARA; MUKHERJEE, A. K. (MAUSAM, 1958)
The meteorological conditions leading to the formation of a rare fog, which caused a spectacular lunar corona at Jodhpur in the ear]y hours of 18 January 1957, have been investigated. The observed reversal of the surface wind just prior to the development of fog is explained. The variation in the angular diameter of the red annulus of the lunar corona at different times showed that the fog was homogeneous soon after formation with a droplet diameter of l8.2 um. It is shown from the changes of the chromatic structure of the corona that the drop size increased rapidly with the ageing of the fog but did not, however, exceed 50 u before its dissipation.